WORD FORMATION PROCESS FOUND in LESTY KEJORA’S CAPTION on INSTAGRAM - Nur Halimah Lubis; Emeliya Sukma Dara Damanik; Aulia Fatin Pakpahan; Nabilla Fauza Nasution; Ega Viorenti Nabilla (Jurnal Serunai Bahasa Inggris, 2022)
This study aims to decipher Word formation Process Found in Lesty Kejora'scaption on Instagram". The method in this study utilizes a qualitative descriptive method, with keep tabs as the next conciliation, we got the data source from Lesty Kejora's captions on Instagram during a year(April 2021—April 2022).In this research, the writers utilizes Yule's theory (1996) for analyzes the word forming found in Lesty Kejora's caption on Instagram, for analyzing 10 word formation processes, they are (1) coinage, (2) borrowing, (3) blending, (4) clipping, (5) acronyms, (6) derivation, (7) compounding, (8) backformation, (9) multiplyprocesses, (10) conversion. To analyze the data, the researcher make the results of classifying the word formation made in the form of a table, so that the researcher analyzed the data. The results displayed that there were 96 words with 65 words Borrowing, 11 compounding, 4 derivation words, 10 acronyms, 1 word blending and 5 clipping words. The dominant type in the word formation process in Lesty Kejora's captions on Instagram is borrowing, which is have 65 data found.